Making marinas bivalve friendly for enhanced biodiversity outcomes. (August 2021) - Adams, L.W.; Morris, R.L.; Hull, R.B.; Dempster, T.; Strain, E.M.A.
Abstract: Natural coastlines are being replaced by artificial structures (pilings, pontoons, breakwaters), with negative environmental impacts, particularly in marinas. Ropes seeded with mussels ( Mytilus galloprovincialis ) were added to artificial structures in a marina, using aquaculture techniques, to reduce the colonisation of invasive taxa. After 6-months, droplines beneath pontoons had the highest seeded mussel survival and growth, richness of native and invasive taxa, and proportion of invasive to native taxa, compared with the other interventions. Mussel ropes on the intertidal structures (pilings and breakwaters) supported higher biomass of native taxa, whereas mussel ropes on subtidal structures (pontoons and breakwaters) had reduced biomass of invasive taxa, relative to the unseeded ropes. Droplines had the greater biomass of mussels, while mussel ropes placed under pontoons, and in subtidal gabion baskets limited the biomass but not the diversity of invasive species. Further study is required to determine whether these interventions can be upscaled to improve both the native biodiversity and functioning of marinas. Graphical abstract: Unlabelled Image Highlights: Mussels were attached to artificial structures in a marina using aquaculture techniques. The eco-engineering interventions had ecological trade-offs. Droplines under pontoons had the largest mussels and highest richness of taxa. Mussel ropes reduced the biomass but not diversity of invasive taxa, subtidally. Eco-engineering interventions should be upscaled to improve the biodiversity and water quality of marinas.